Compliance in the public versus the private realm: Economic preferences, institutional trust and COVID-19 health behaviors - Henrike Sternberg; Janina Isabel Steinert; Tim Büthe (Health Economics, 2024)
To what extent do economic preferences and institutional trust predict compliance with physical distancing rules during the COVID-19 pandemic? We reexamine this question by introducing the theoretical and empirical distinction between individual health behaviors in the public and in the private domain (e.g., keeping a distance from strangers vs. abstaining from private gatherings with friends). Using structural equation modeling to analyze survey data from Germany's second wave of the pandemic (N = 3350), we reveal the following major differences between compliance in both domains: Social preferences, especially (positive) reciprocity, play an essential role in predicting compliance in the public domain but are barely relevant in the private domain. Conversely, individuals' degree of trust in the national government matters predominantly for increasing compliance in the private domain. The clearly strongest predictor in this domain is the perception pandemic-related threats. Our findings encourage tailoring communication strategies to either domain-specific circumstances or factors common across domains. Tailored communication may also help promote compliance with other health-related regulatory policies beyond COVID-19.
Keywords: 330; compliance; COVID-19; economic preferences; health behavior; institutional trust; physical distancing